Greenwich Village 1963 : avant-garde performance and the effervescent body - Banes, Sally (Duke University Press, 1993)
The year was 1963 and from Birmingham to Washington, D.C., from Vietnam to the Kremlin to the Berlin Wall, the world was in the throes of political upheaval and historic change. But that same year, in New York's Greenwich Village, another kind of history and a different sort of politics were being made. This was a political history that had nothing to do with states or governments or armies--and had everything to do with art. And this is the story that Sally Banes tells, a year in the life of American culture, a year that would change American life and culture forever. It was in 1963, as Banes's book shows us, that the Sixties really began. A leading writer on cultural history, Banes draws a vibrant portrait of the artists and performers who gave the 1963 Village its exhilarating force, the avant-garde whose interweaving of public and private life, work and play, art and ordinary experience, began a wholesale reworking of the social and cultural fabric of America. Among these young artists were many who went on to become acknowledged masters in their fields, including Andy Warhol, John Cage, Yoko Ono, Yvonne Rainer, Lanford Wilson, Sam Shepard, Brian de Palma, Harvey Keitel, Kate Millet, and Claes Oldenburg. In live performance--Off-Off Broadway theater, Happenings, Fluxus, and dance--as well as in Pop Art and underground film, we see this generation of artists laying the groundwork for the explosion of the counterculture in the late 1960s and the emergence of postmodernism in the 1970s. Exploring themes of community, freedom, equality, the body, and the absolute, Banes shows us how the Sixties artists, though shaped by a culture of hope and optimism, helped to galvanize a culture of criticism and change. As 1963 came to define the Sixties, so this vivid account of the year will redefine a crucial generation in recent American history.